Pharmacological targeting netrin-1 inhibits EMT in cancer - Lengrand, Justine (Nature, 2023)
Epithelial-to-mesenchymal transition (EMT) regulates tumour initiation, progression, metastasis and resistance to anti-cancer therapy(1–7). Although great progress has been made in understanding the role of EMT and its regulatory mechanisms in cancer, no therapeutic strategy to pharmacologically target EMT has been identified. Here we found that netrin-1 is upregulated in a primary mouse model of skin squamous cell carcinoma (SCC) exhibiting spontaneous EMT. Pharmacological inhibition of netrin-1 by administration of NP137, a netrin-1-blocking monoclonal antibody currently used in clinical trials in human cancer (ClinicalTrials.gov identifier NCT02977195), decreased the proportion of EMT tumour cells in skin SCC, decreased the number of metastases and increased the sensitivity of tumour cells to chemotherapy. Single-cell RNA sequencing revealed the presence of different EMT states, including epithelial, early and late hybrid EMT, and full EMT states, in control SCC. By contrast, administration of NP137 prevented the progression of cancer cells towards a late EMT state and sustained tumour epithelial state. Short hairpin RNA knockdown of netrin-1 and its receptor UNC5B in EPCAM(+) tumour cells inhibited EMT in vitro in the absence of stromal cells and regulated a common gene signature that promotes tumour epithelial state and restricts EMT. To assess the relevance of these findings to human cancers, we treated mice transplanted with the A549 human cancer cell line—which undergoes EMT following TGFβ1 administration(8,9)—with NP137. Netrin-1 inhibition decreased EMT in these transplanted A549 cells. Together, our results identify a pharmacological strategy for targeting EMT in cancer, opening up novel therapeutic interventions for anti-cancer therapy.